INTEGRATION OF EVIDENCE-BASED PRACTICE IN BEDSIDE TEACHING PAEDIATRICS SUPPORTED BY E-LEARNING - Potomkova, Jarmila; Mihal, Vladimir; Zapletalova, Jirina; Subova, Dana (Biomedical papers, 2010)
Background: Bedside teaching with evidence-based practice elements, supported by e-learning activities, can play an important role in modern medical education. Teachers have to incorporate evidence from the medical literature to increase student motivation and interactivity.Materials and Methods: An integral part of the medical curricula at Palacky University Olomouc (Czech Republic) are real paediatric scenarios supplemented with a review of current literature to enhance evidence-based bedside teaching & learning. Searching for evidence is taught through librarian-guided interactive hands-on sessions and/or web-based tutorials followed by clinical case presentations and feedback.Results: Innovated EBM paediatric clerkship demonstrated students' preferences towards web-based interactive bedside teaching & learning. In two academic years (2007/2008, 2008/2009), learning-focused feedback from 106 and 131 students, resp. was obtained about their attitudes towards evidence-based bedside teaching. The assessment included among others the overall level of instruction, quality of practical evidence-based training, teacher willingness and impact of instruction on increased interest in the specialty. There was some criticism about excessive workload. A parallel survey was carried out on the perceived values of different forms of information skills training (i.e. demonstration, online tutorials, and librarian-guided interactive search sessions) and post-training self-reported level of search skills.Conclusion: The new teaching/learning paediatric portfolio is a challenge for further activities, including effective knowledge translation, continuing medical & professional development of teachers, and didactic, clinically integrated teaching approaches.
Keywords: Bedside teaching≤arning/Information technology/e-Learning activities/Evidence-based practice/Paediatriccurriculum/Web-based learning/Search skills training